2011
DOI: 10.1007/s00436-011-2490-5
|View full text |Cite
|
Sign up to set email alerts
|

Ancyrocephalidae (Monogenea) of Lake Tanganyika: II: description of the first Cichlidogyrus spp. parasites from Tropheini fish hosts (Teleostei, Cichlidae)

Abstract: Although Lake Tanganyika hosts the most diverse endemic cichlid fish assemblage, its monogenean parasite fauna has hardly been documented. The cichlid tribe Tropheini has generated great interest because of its systematic position within the Haplochromini s.l. and its diversity in trophic morphology, reproductive behaviour and population structure. It has the potential to host a diverse Monogenea fauna. Here, we describe the first Cichlidogyrus spp.: Cichlidogyrus steenbergei sp. n., Cichlidogyrus irenae sp. n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
59
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 28 publications
(40 reference statements)
2
59
1
2
Order By: Relevance
“…This is a limited number compared to the more than 400 valid Gyrodactylus spp. worldwide (Harris et al 2004), or to the 78 species of Cichlidogyrus Paperna, 1960 in Africa, Madagascar and the Levant (Pariselle and Euzet 2009;Vanhove et al 2011b;Gillardin et al 2011). C. gariepinus is known to host five African Gyrodactylus species.…”
Section: Introductionmentioning
confidence: 98%
“…This is a limited number compared to the more than 400 valid Gyrodactylus spp. worldwide (Harris et al 2004), or to the 78 species of Cichlidogyrus Paperna, 1960 in Africa, Madagascar and the Levant (Pariselle and Euzet 2009;Vanhove et al 2011b;Gillardin et al 2011). C. gariepinus is known to host five African Gyrodactylus species.…”
Section: Introductionmentioning
confidence: 98%
“…Although the first record of parasitic flatworms in Lake Tanganyika stems from a study on cestodes from 19149, the knowledge about the diversity and role of parasitic organisms in this unique environment is still poor and fragmentary. In the last years, parasitological research in the lake has mainly focused on the monogenean fauna of its cichlids and the number of described species is increasing101112131415161718. Monogenea van Beneden, 1858 is one of the most species-rich groups of Platyhelminthes1920 with more than 3,500 already described species21.…”
mentioning
confidence: 99%
“…Currently, 13 monogenean genera are known to infect cichlid species and six of these have been observed on African representatives36. Cichlidogyrus (Monopisthocotylea, Dactylogyridae) is the most species rich, with 102 representatives recorded from 88 different host species10111213141518373839404142. This genus displays variation in host-specificity and contains generalist but also strictly specialist species3943.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lake Tanganyika's spectacular cichlid species flock likely hosts an even more diverse parasite community. The monogenean genus Cichlidogyrus appears to be particularly species rich, and previous studies have demonstrated extremely high levels of host specificity in the megadiverse littoral cichlid communities (Gillardin et al, 2011;Vanhove et al, unpublished). Here, Pariselle et al (2015) describe a new Cichlidogyrus species and show that this species parasitizes a range of distantly related host species within the benthopelagic deepwater cichlid genus Bathybates, suggesting that reduced host specificity may represent an adaptation to low host availability in deep water habitat.…”
Section: East African Great Lakesmentioning
confidence: 99%